Exploring Nursing Students' Perspectives on Patient Safety Culture in Clinical Settings: A Mixed-Method Study - Bartoníčková, Daniela; Kohanová, Dominika; Cakirpaloglu, Simona Dobešová; Steven, Alison; Žiaková, Katarína (Journal of clinical nursing, 2025)
BACKGROUND: Patient safety in undergraduate nursing studies is an indispensable component of the curriculum. The process of experiential learning from practice is of high value not only in terms of personal development but also enables students to identify and address critical areas of patient safety that require improvement. AIM: To explore Czech undergraduate nursing students' perceptions of patient safety culture during clinical practice through a mixed-method sequential study. METHODS: Data were collected between 2021 and 2024 using a mixed-method approach. The quantitative phase utilised the hospital survey on patient safety culture for nursing students. Four hundred and eighty-two undergraduate nursing students from 16 faculties across the Czech Republic participated. The subsequent qualitative phase employed semi-structured interviews with 12 undergraduate nursing students from one faculty in the Czech Republic. Descriptive and inferential statistical methods were used to analyse quantitative results, complemented by a reflective thematic analysis of qualitative data. RESULTS: The most negatively rated survey dimensions were 'Frequency of events reported' (37.0%) and 'Nonpunitive responses to errors' (42.4%). Predictors for reporting adverse events in clinical practice were 'Indicators of good practice' (p ≤ 0.05). Based on the quantitative phase, the interpretive journey of nursing students' experiences from Exposure to adverse events, through Feeling disconnected and Cognitive dissonance, to the necessity of Speaking up for patient safety culture was captured in the qualitative phase. CONCLUSIONS: Nursing students struggle to engage in a patient safety culture, particularly in reporting adverse events during clinical practice. Strengthening education on reporting and standards is essential for students, along with professional development for clinical staff to align practices and cultures.
Keywords: dospělí; Qualitative Research; průzkumy a dotazníky; Female; postoj zdravotnického personálu; Adult; mixed‐method study; mladý dospělý; ženské pohlaví; nursing student; Surveys and Questionnaires; lidé; Education, Nursing, Baccalaureate; studium ošetřovatelství bakalářské; clinical setting; experience; bezpečnost pacientů; patient safety; Attitude of Health Personnel; Students, Nursing; Male; Czech Republic; Young Adult; Česká republika; studenti ošetřovatelství; mužské pohlaví; Patient Safety; kvalitativní výzkum; Humans